Urgensi Pendidikan Tauhid sebagai Dasar Pembentukan Karakter Anak - Firdiana, Linda; Isrofuzain, Isrofuzain; Anshory, M. Isa (TSAQOFAH, 2025)
Tauhid education is the fundamental foundation in Islam that must be instilled from an early age as a life guideline and as a form of belief that only Allah is worthy of worship and that Prophet Muhammad is His messenger. This study aims to examine the concept of aqidah tauhid, methods for internalizing tauhid values in children, guidance from the Qur’an and Hadith regarding its application, and the urgency of aqidah tauhid as the core of Islamic education. The research employed a library study method by collecting, analyzing, and synthesizing various references from scholarly journals, publications, and books relevant to the topic. The findings indicate that tauhid education not only strengthens faith but also forms the moral and spiritual foundation of children, enabling them to live as obedient servants of Allah and as individuals who contribute positively to society. The internalization of tauhid values can be carried out through exemplary behavior, habituation, advice, and emotional approaches aligned with the child’s developmental stage. Tauhid-based education grounded in the Qur’an and Hadith serves as the main pillar in shaping children into pious and morally upright individuals. These findings offer valuable insights for educators and parents in optimizing the systematic and holistic inculcation of tauhid values in children's education.